2012
DOI: 10.1074/jbc.m112.353888
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Modulation of Gating Property of G Protein-gated Inwardly Rectifying Potassium Ion Channel (GIRK) by i/o-family G Protein α Subunit (Gαi/o)

Abstract: Background: Although G␤␥ is known to activate GIRK, G␣ i/o also modulates GIRK gating. Results: The ␣2/␣3 helices of G␣ i3 in the GTP-bound state directly bind to the ␣A helix of GIRK. Conclusion:The complex model explains how G␣ i/o sequesters G␤␥ efficiently from GIRK upon GTP hydrolysis. Significance: The structural basis for the rapid closure of GIRK by G␣ i/o is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…Previous studies had similarly reported that inactive Ga did not directly interact with Kir3.1/3.2 subunits (Fowler et al, 2007;Berlin et al, 2011) and had proposed that this subunit associates with Kir3 channels via the Gbg dimer (Berlin et al, 2011). On the other hand, NMR studies have revealed a direct interaction between the switch 2 region of GTP-bound Gai3 and the aA helix of Kir3.1 subunits (Mase et al, 2012), suggesting that Ga and the channel may come into direct contact on G protein activation. We did not find evidence for this type of reorganization since DOR stimulation by highly efficacious agonists failed to show BRET at the GaoA/Kir3.1 interface.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies had similarly reported that inactive Ga did not directly interact with Kir3.1/3.2 subunits (Fowler et al, 2007;Berlin et al, 2011) and had proposed that this subunit associates with Kir3 channels via the Gbg dimer (Berlin et al, 2011). On the other hand, NMR studies have revealed a direct interaction between the switch 2 region of GTP-bound Gai3 and the aA helix of Kir3.1 subunits (Mase et al, 2012), suggesting that Ga and the channel may come into direct contact on G protein activation. We did not find evidence for this type of reorganization since DOR stimulation by highly efficacious agonists failed to show BRET at the GaoA/Kir3.1 interface.…”
Section: Discussionmentioning
confidence: 94%
“…DOR-Evoked Changes at the Gbg/Kir3 Subunit Interface are Concomitant with Conformational Rearrangements Among GaoA/Gbg Subunits and Predictive of Ligand Ability to Induce Channel Currents. Ga subunits are thought to modulate channel activity both through direct interaction with Kir3 subunits and by making Gbg readily available in the proximity of channel subunits (Peleg et al, 2002;Clancy et al, 2005;Rubinstein et al, 2009;Mase et al, 2012). We were therefore interested in characterizing whether DOR activation modified Ga interactions with different complex components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5, A and B). The Gbg binding sites on Kir3 channels have also been investigated by NMR (Yokogawa et al, 2011;Mase et al, 2012). By mapping the residues affected by Gbg binding to the structure, the authors proposed that Gbg binds at the interface between adjacent subunits allowing for contacts with the N terminus of one subunit and the C terminus of an adjacent subunit.…”
Section: A Kir3 Channelsmentioning
confidence: 99%
“…GIRK channels are opened by G␤␥ subunits and closed by channelbound G i/o ␣ subunits that have hydrolyzed GTP to GDP and reformed G␣␤␥ heterotrimers (37,38). By accelerating G i/o ␣- Palmitate Turnover Regulates GPCR-GIRK Signaling FEBRUARY 28, 2014 • VOLUME 289 • NUMBER 9 mediated GTP hydrolysis, R7 RGS-G␤5 complexes recruited to GIRK channels by R7BP facilitate channel closure (26).…”
Section: Palm B or Hdfp Enters Cells And Inactivates Serine Hydrolasementioning
confidence: 99%